Eimeria species in dairy and beef cattle of different ages in Goiás state, Brazil - Cruvinel, Leonardo Bueno; Nicaretta, João Eduardo; Bastos, Thiago de Souza Azeredo; Couto, Luiz Fellipe Monteiro; Dos Santos, Jordana Belos; Zapa, Dina María Beltrán; Cavalcante, Alliny Souza de Assis; Cruz, Breno Cayeiro [UNESP]; Borges, Dyego Gonçalves Lino; Borges, Fernando de Almeida; Soares, Vando Edésio; Lopes, Welber Daniel Zanetti (FapUNIFESP (SciELO), 2018)
This study aimed to identify the frequency of occurrence of Eimeria species in Holstein (taurine dairy cattle) and Nelore (zebu beef cattle) on 12 farms in the state of Goiás, Brazil. A total of 2,601 animals were evaluated, and the cattle were divided into the following age-group categories: up to three months old, four to eight months old, nine to 16 months old and cows. Fecal samples were collected directly from the rectum of all animals. None of the cattle presented any clinical signs of eimeriosis during the survey. From the results obtained, it could be concluded that higher rates of infection by Eimeria spp. were observed in Holstein cattle between the 1st and 16th months of age and in Nelore cattle between the 1st and 8th months of age. Twelve and nine Eimeria species were diagnosed in Holstein and Nelore cattle, respectively. However, Eimeria zuernii was more prevalent in animals up to three months old, while Eimeria bovis was more common in the remaining categories (cattle aged four months and over). Future studies on the epidemiology and/or seasonality of infection by Eimeria species in cattle, from birth onwards, are needed in order to better understand the dynamics of E. zuernii and E. bovis occurrences, especially in cattle under three months of age.
Espécies de Eimeria em bovinos de leite e corte de diferentes idades no Estado de Goiás, Brasil
Keywords: Calves; Eimeria bovis; Eimeria zuernii; Eimeriosis; OoPG